ZEOLITE-MODIFIED CARBON PASTE ELECTRODE FOR DETERMINATION OF COPPER USING ANODIC STRIPPING VOLTAMMETRY METHOD - Irdhawati Irdhawati; Hery Suyanto; Putu Yani Andani (UNIVERSITAS SEBELAS MARET (UNS), 2017)
In this research, the unmodified and modified carbon paste electrode with zeolite has been prepared, for determination of Cu(II) using anodic stripping voltammetry method. The parameters observed involved deposition time, scan rates, zeolite composition in carbon paste, and validation of working electrode. The optimum performance of carbon paste electrode modified with zeolite was applied for determination of Cu(II) in wastewater of the gong fabrication. The results of this research showed the optimum of deposition time and scan rates obtained at 410 s and 7.5 mV/s for unmodified carbon paste electrode, respectively. The optimum composition of zeolite-modifier is 20% from total graphite, with deposition time 380 s and scan rates 10 mV/s. The detection limit of the measurement of Cu(II) standard solution using unmodified carbon paste electrode is 46.13 ppb, is lower than unmodified carbon paste electrode, 99.93 ppb. Zeolite-modified carbon paste electrode has good precision and accuration. The concentration of Cu(II) in waste water of gong fabrication , using carbon paste electrode modified with zeolite is 93.54 ± 0.87 ppb.